DETERMINATION OF CHANGES IN INTERMOLECULAR "FREE VOLUME" OF LIQUIDS AT DIFFERENT PRESSURES FROM HYPERACOUSTIC DATA (Academicia Globe: Inderscience Research, 2024)
A great contribution to the study of the liquid state can be made by finding out the nature of the change in the intermolecular space (free volume) between liquid molecules at various state parameters. Optical methods will give us the opportunity to obtain more complete information about the nature of the change in the free volume between the molecules of liquids. One of these methods is based on the study of the Mandelstam-Brillouin light scattering spectra. In the work, the velocities of hypersonic propagation along the Mandelstam-Brilyuin spectra of light scattering were investigated, and on the basis of the hypersonic velocity, the volume of micro voids (free volume) between liquid molecules was calculated. As can be seen from the results obtained, with an increase in pressure and molecular weight of alcohols, the volume of micro voids between the liquid molecules decreases. This is fully consistent with the main provisions of the hole theory of J.I. Frenkel.